2022
DOI: 10.3390/ijms23094925
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of Microglia and Its Therapeutic Potential in Sepsis

Abstract: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection, leaving the inflammation process without a proper resolution, leading to tissue damage and possibly sequelae. The central nervous system (CNS) is one of the first regions affected by the peripheral inflammation caused by sepsis, exposing the neurons to an environment of oxidative stress, triggering neuronal dysfunction and apoptosis. Sepsis-associated encephalopathy (SAE) is the most frequent sepsis-associated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…During sepsis, inflammatory factors and signals reach different regions of the brain through various means, such as body fluids and nerves ( 16 ). Neuroinflammation plays a vital role in the pathogenesis of SAE, as uncontrolled inflammatory responses are the main manifestations of sepsis.…”
Section: Mechanism Of Sepsis-associated Encephalopathymentioning
confidence: 99%
“…During sepsis, inflammatory factors and signals reach different regions of the brain through various means, such as body fluids and nerves ( 16 ). Neuroinflammation plays a vital role in the pathogenesis of SAE, as uncontrolled inflammatory responses are the main manifestations of sepsis.…”
Section: Mechanism Of Sepsis-associated Encephalopathymentioning
confidence: 99%
“…Therefore, revealing the pathogenesis of SAE is of great significance. Microglia activation is critical to neuroinflammation and SAE development [20,21]. At present, some studies have revealed that the inhibition of microglia activation can alleviate the SAE process.…”
Section: Discussionmentioning
confidence: 99%
“…Activated microglial cells are very plastic and may exist in multiple phenotypes, ranging from pro-inflammatory(M1) cell population releasing nitric oxide, TNF-α and IL-1β to antiinflammatory subtype releasing IL-10 or IL-4. The proinflammatory phenotypes are usually considered to be neurotoxic whereas M2 phenotype may contribute to neuroprotection [9,10]. Consistently, the inhibition of M1 polarization by an intracerebroventicular(i.c.v) injection of minocycline suppressed the oxidative damage, neuroinflammation and long-term cognitive impairments in septic rats [11].Thus, modulation of microglia activation may provide with a promising approach in treating SAE.…”
Section: Introductionmentioning
confidence: 92%